Splatoon. Vol. 13 - Hinodeya, Sankichi; Turnage, Bryant (Hinodeya, Sankichi. Splatoon, 2021)
"The search for the hidden treasure of Sheldon's grandfather continues. To complete their quest, Goggles will have to defeat the diabolical Eye of Justice, who is proving to be a wily and worthy foe! Can Goggles defeat the Eye of Justice, unlock the secret of Ammoses Shellendorf's treasure, and advance to the Final Splatfest?!"--Back cover